(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Surgical Site Infection (SSI) is one of the most common healthcare-associated infections, with significant morbidity, death and economic consequences. Antibiotic resistance is a growing problem nowadays, affecting SSI management and its control. This study aims to identify the bacterial profile, antimicrobial susceptibility and resistance pattern of SSI patients at Chittagong Medical College Hospital, Chattogram, Bangladesh. Materials and methods: This cross-sectional study was conducted in the Surgery Outpatient Department of Chittagong Medical College Hospital. 137 wound swabs on a sterile cotton swab were collected from the surgical wounds of the patients and were processed following standard laboratory techniques. The identification of every individual bacterium was conducted by assessing colony features, gram stain, conventional biochemical assays, and antibiotic susceptibility testing using the disc diffusion technique. Results: The study found that 88.3% of patients were found culture positive and 11 types of organisms were identified, with 62.8% showing Gram-negative organisms and 25.5% showing Gram-positive organisms. The frequency of commonly occurring different isolated bacteria revealed the presence of Pseudomonas bacteria in 31% cases, Staph. aureus in 17% cases and E. coli in 16%. A statistically significant association with antibiotic resistance was found regarding not maintenance of proper antibiotic dose and duration, history of indiscriminate antibiotic intake and irregular wound dressing after surgery (p<0.05). Conclusion: A high prevalence of gram-negative organism infection was noted in SSI patients, with most commonly identified bacteria showing resistance to commonly used antibiotics. An increased prevalence of antibiotic resistance is observed among patients with a history of taking irrational antibiotics. JCMCTA 2024 ; 35 (1) : 82-88